IMPROVING SOCIAL STUDIES LEARNING OUTCOMES THROUGH THE INDEX CARD MATCH MODEL FOR FIFTH GRADE STUDENTS OF SD NEGERI 67 LUBUKLINGGAU - Fela Novita (CV Grasta Glory, 2026)
This study aims to improve fifth-grade students' social studies learning outcomes through the Index Card Match learning model at SD Negeri 67 Lubuklinggau. Quantitative research using an experimental approach was used, with 21 fifth-grade students as subjects. Data collection techniques used were observation, interviews, documentation, and tests. Data analysis techniques were also used. This study consisted of two pre-experiments, each consisting of four stages: planning, implementation, observation, and reflection. In the first pre-experiment, the pre-test stage had a percentage of 14.28% in the very low category, and in the post-test stage, a percentage of 33.33% in the low category. Meanwhile, in the second pre-experiment, the pre-test stage showed a percentage of 71.42% in the moderate category. Then, in the post-test, student learning outcomes increased, with 80.95% in the very high category. The results of this study indicate an increase in student learning outcomes using the Index Card Match learning model for fifth-grade students at SD Negeri 67 Lubuklinggau.